Blended home‐based exercise and dietary protein in community‐dwelling older adults: a cluster randomized controlled trial. Issue 6 (26th October 2020) - van den Helder, Jantine; Mehra, Sumit; van Dronkelaar, Carliene; ter Riet, Gerben; Tieland, Michael; Visser, Bart; Kröse, Ben J.A.; Engelbert, Raoul H.H.; Weijs, Peter J.M.
Abstract: Background: Effective and sustainable interventions are needed to counteract the decline in physical function and sarcopenia in the growing aging population. The aim of this study was to determine the 6 and 12 month effectiveness of blended (e‐health + coaching) home‐based exercise and a dietary protein intervention on physical performance in community‐dwelling older adults. Methods: This cluster randomized controlled trial allocated 45 clusters of older adults already engaged in a weekly community‐based exercise programme. The clusters were randomized to three groups with ratio of 16:15:14; (i) no intervention, control (CON); (ii) blended home‐based exercise intervention (HBex); and (iii) HBex with dietary protein counselling (HBex‐Pro). Both interventions used a tablet PC with app and personalized coaching and were targeting on behaviour change. The study comprised coached 6 month interventions with a 6 month follow‐up. The primary outcome physical performance was assessed by modified Physical Performance Test (m‐PPT). Secondary outcomes were gait speed, physical activity level (PAL), handgrip muscle strength, protein intake, skeletal muscle mass, health status, and executive functioning. Linear mixed models of repeated measured were used to assess intervention effects at 6 and 12 months. Results: The population included 245 older adults (mean age 72 ± 6.5 (SD) years), 71% female, and 54% co‐morbidities observed. Dropout of the intervention was 18% at 6 months and 26% at 12 months. Participants were well functioning, based on an m‐PPT score of 33.9 (2.8) out of 36. For the primary outcome m‐PPT, no significant intervention effects (HBex, +0.03, P  = 0.933; HBex‐Pro, −0.13, P  = 0.730) were found. Gait speed (+0.20 m/s, P  = 0.001), PAL (+0.06, P  = 0.008), muscle strength (+2.32 kg, P  = 0.001), protein intake (+0.32 g/kg/day, P  < 0.001), and muscle mass (+0.33 kg, P  = 0.017) improved significantly in the HBex‐Pro group compared with control group after 6 month intervention. The protein intake, muscle mass, and strength remained significantly improved after 12 months as compared with those of control. Health change and executive functioning improved significantly in both intervention groups after 6 months. Conclusions: This HBex and dietary protein interventions did not change the physical performance (m‐PPT) in community‐dwelling older adults. Changes were observed in gait speed, PAL, muscle mass, strength, and dietary protein intake, in response to this combined intervention.